2021
DOI: 10.1007/s11845-021-02660-w
|View full text |Cite|
|
Sign up to set email alerts
|

A cross-section observational study on the seroprevalence of antibodies to COVID-19 in patients receiving opiate agonist treatment

Abstract: Introduction The HSE National Drug Treatment Centre is an inner city drug treatment centre in Dublin which provides opiate agonist treatment (OAT) to approximately 565 patients, many of whom have complex care needs. Objective This study was conducted to determine seropositivity to the COVID-19 virus in patients attending NDTC, and to establish if patients tested had any clinical symptoms of this disease since March 2020. Method All patients attending for OAT were invited to participate and 103/565 patients agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Second, in this study, more than 1600 drug addicts were included. This number is quite high compared to previous studies investigating prevalence rates of SARS-CoV-2 in Switzerland (n = 122; [11] and Ireland (n = 103, [12]). However, compared to populationbased samples, which were calculated in 100,000 persons, our sample is relatively small.…”
Section: Limitationsmentioning
confidence: 56%
See 2 more Smart Citations
“…Second, in this study, more than 1600 drug addicts were included. This number is quite high compared to previous studies investigating prevalence rates of SARS-CoV-2 in Switzerland (n = 122; [11] and Ireland (n = 103, [12]). However, compared to populationbased samples, which were calculated in 100,000 persons, our sample is relatively small.…”
Section: Limitationsmentioning
confidence: 56%
“…Eventually, the observation period was about 12 months compared to 4–5 months in previous studies in Ireland 12 and Switzerland 11 , respectively. In addition, our data were gathered from several centres instead of a monocentric approach.…”
Section: Limitationsmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, COVID-19 symptoms are more or less unspecific and very close to those of an opioid withdrawal; they might not be perceived as such of a COVID-19 infection [6]. While Fenton et al [23] tested in an Irish study of 103 patients at a national drug treatment center, only two individuals with positive SARS-CoV-2 antibodies, Bruggmann et al [24] found a more than twofold higher SARS-CoV-2 seroprevalence among OAT patients (9.8%) in Zurich (Switzerland) compared to the general population (3.5%), whereas both studies did not identify patients with a severe disease progression. A nationwide cohort study in the USA suggests that people with OUD and COVID-19 have a higher risk of worse COVID-19 outcomes and that especially younger age and no medication treatment for OUD are risk factors for dying due to COVID-19 [25].…”
Section: Discussionmentioning
confidence: 99%